Spiritualitas dan Pembelajaran Agama Islam: Kajian Haflah Akhirussanah di Madrasah Diniyah dan Pondok Pesantren - Tegar Sasario Pamungkas; Tri Seno Anjanarko; Jahroni Jahroni; Samsul Arifin; Arif Rachman Putra; Rommy Hardyansah (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
This study describes the activities to improve the understanding of religious knowledge held by madrasah diniyah and boarding school Nurul Huda At-Tahdzihiy Larangan Bareng Jombang. Using a descriptive qualitative approach with observation and documentation techniques, the research shows the effectiveness of the institution in improving the religious understanding of the students before the month of Ramadan. This activity, held in the month of Sha'ban, aims to prepare students to welcome the holy month of Ramadan efficiently.